1995
DOI: 10.1530/jrf.0.1050025
|View full text |Cite
|
Sign up to set email alerts
|

Identification of male germ cells undergoing apoptosis in adult rats

Abstract: The possible role of apoptosis in spontaneous or induced germ cell death was investigated by treating adult male rats with either a GnRH antagonist (112.5 micrograms kg-1 day-1 for 14 days) or methoxyacetic acid (650 micrograms kg-1; single dose) or sham-treated with either of the vehicles (n = 3 per group). The antagonist virtually abolished gonadotrophin secretion, while methoxyacetic acid reduced serum testosterone concentrations and slightly increased those of FSH (neither significantly). Bands of low mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
2
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 28 publications
11
125
2
1
Order By: Relevance
“…Our initial studies led us to ethylene glycol monomethyl ether (EGME), a pervasive industrial solvent found in varnishes, paints, dyes, and fuel additives. Exposure to this compound and its primary metabolite MAA induce severe reproductive toxicity in both humans and rodents (11,12). Based on reports that toxic doses of EGME give rise to 5 mM MAA plasma levels in rodents and that similar concentrations of MAA are observed in the urine of humans after occupational EGME exposure (13,14), we treated cells with 5 mM MAA to achieve comparable MAA levels for our studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our initial studies led us to ethylene glycol monomethyl ether (EGME), a pervasive industrial solvent found in varnishes, paints, dyes, and fuel additives. Exposure to this compound and its primary metabolite MAA induce severe reproductive toxicity in both humans and rodents (11,12). Based on reports that toxic doses of EGME give rise to 5 mM MAA plasma levels in rodents and that similar concentrations of MAA are observed in the urine of humans after occupational EGME exposure (13,14), we treated cells with 5 mM MAA to achieve comparable MAA levels for our studies.…”
Section: Resultsmentioning
confidence: 99%
“…Serum samples were assayed for testosterone and FSH concentrations using RIA as described (Brinkworth et al 1995, Chandolia et al 1991a. Limit of detection, and inter-and intra-assay coefficients of variation for testosterone assays were 0·67 nmol/l, 7·5% and 9·2% respectively.…”
Section: Testicular Volumes and Serum Hormone Concentrationsmentioning
confidence: 99%
“…Doxorubicin (DXR), an anthracycline that is a cornerstone of many chemotherapeutic regimens, is used for treating a wide spectrum of malignancies including both hematological and solid tumors. DXR has been previously studied for its deleterious effect on the gonadal epithelium in rodents, where it was shown to cause chromosome aberrations in spermatogonial cells (Au & Hsu 1980, Abraham & Fränz 1983, inhibition of DNA synthesis and induction of apoptosis (Brinkworth et al 1995, Blanco-Rodríguez & Martínez-García 1996, Shinoda et al 1999, Hou et al 2005. DXR has been shown to disrupt sperm maturation, reduce epididymal sperm concentration as well as alter spermatogonial DNA and sperm morphology (Meistrich et al 1990).…”
Section: Introductionmentioning
confidence: 99%